The Influence of Political Messages in New Media to Political Awareness and Its Impact on the Political Participation of Millennial Generation - Nur Kholisoh; Elly Yuliawati; Nurfa Rachma Suci; Tri Suharman (Jurnal Komunikasi Ikatan Sarjana Komunikasi Indonesia, 2019)
Today many political parties use new media, the internet, as their political communication channel.  For young people, the internet serves as a dominant public space. Since young voters as millennial generation have great potential to increase votes, many political parties convey their political messages through new media used by millennial generation. This research is intended to see and study the influence of political messages in new media on political awareness and its impact on political participants of millennial generation. This research uses Stimulus Organism Response (S-O-R) theory as main theory, McQuail’s mass communication theory, and theory or concept of political awareness, political participation and new media as well as millennial generation. This research uses quantitative approaches with a survey and questionnaire method as a means of collecting data. The millennial generation referred to in this research is younger generation aged between 17 and 37 years and lives in the Special Capital Province of Jakarta (DKI Jakarta). Based on the recapitulation of final voter lists for the 2018 general election, the number of voters aged between 17 and 37 years reaches about 2,885,000. The technique of determining the sample size uses Slovin’s formula, with the margin of error reaching 5% so that the number of samples is 400. Meanwhile, the technique of sampling uses proportional sampling and data analysis technique uses path analysis. The results of the research show that political messages in new media have direct and indirect influences on the political participation of millennial generation.